Bone health and deterioration in quality of life among participants from the Hertfordshire cohort study. - Dennison, E; Jameson, K; Syddall, H; Martin, H; Cushnaghan, J; Aihie Sayer, A; Cooper, C (2010)
UNLABELLED: We utilised the Hertfordshire cohort study to examine relationships between bone density at baseline and SF-36 status 4 years later. We found deterioration in the mental health domain over follow-up in osteoporotic men (but not women) compared with other groups (relative rate ratio=5.78, 95% confidence interval (CI) 1.78-19.2). INTRODUCTION: Osteoporosis is associated with decreased quality of life, although it has been difficult to evaluate the confounding effects of fracture and co-morbidity. Having previously shown that male osteoporotics have poorer health than counterparts with normal bone mineral density, even after adjustment for co-morbidity and prior fracture, we assessed quality of life in both groups 4 years apart. METHODS: Four hundred and ninety-eight men and 468 women completed questionnaires detailing lifestyle factors, co-morbidities and quality of life (SF-36) before undergoing bone density measurements at the lumbar spine and total femur. At follow-up 4 years later, 322 men and 320 women were reassessed. RESULTS: Multinomial logistic regression confirmed deterioration in mental health over follow-up in osteoporotic men compared with other groups (relative rate ratio=5.78, 95% CI 1.78-19.2). These patterns were not apparent among women. CONCLUSIONS: Men with lower bone density at baseline had poorer quality of life some 4 years later, even after adjustment for co-morbidity and fracture. This may reflect secondary osteoporosis in men (due to alcohol or hypogonadism).